National Crime Surveys: National Sample of Rape Victims, 1973-1982 ([Verlag nicht ermittelbar], 1987)
The purpose of this study was to provide an in-depth look at rapes and attempted rapes in the United States. Part 1 of the collection offers data on rape victims and contains variables regarding the characteristics of the crime, such as the setting, the relationship between the victim and offender, the likelihood of injury, and the reasons why rape is not reported to police. Part 2 contains data on a control group of females who were victims of no crime or of crimes other than rape. The information contained is similar to that found in Part 1.